P032 The Health Belief Model for Shift Workers Scale: The development and validation of a novel metric for use in shift working populations. (9th November 2022) - Crowther, M; Ferguson, S; Gupta, C; Reynolds, A
Abstract: Introduction: Shift work is associated with circadian misalignment, sleep loss and suboptimal health behaviours, which may contribute to longer term negative health outcomes. interventions based on behavioural models may improve health behaviours in shift workers. To implement and evaluate these interventions, a validated metric based on behavioural theory specifically for use with shift workers would be beneficial. The present study aimed to develop and evaluate the Health Belief Model for Shift Workers (HBM-SW) scale. Methods: The HBM-SW development involved a seven-step process, including a literature review, expert panel analysis, cognitive interviews with shift workers, and administration to pilot sample of shift workers (n=153). Validation of the HBM-SW was compared to Pittsburgh Sleep Quality Index, International Physical Activity Questionnaire and Food Frequency Questionnaire. Results: Utilising exploratory factor analysis for factor identification and item reduction, the developed scale loaded on seven factors in line with the theoretical framework of the Health Belief Model: Perceived Threat, Perceived Severity, Perceived Benefits, Perceived Barriers, Cues to Action, Self-Efficacy and Health Motivation. The HBM-SW showed good – excellent (α =0.74-0.93) internal consistency and moderate – good (ICC =0.64-0.89) test re-test reliability. Using health behaviour outcome measures, the HBM-SW scale showed meaningful correlations with sleep quality, sleep duration, diet quality and leisure time physical activity, and acceptable validity and reliability. Conclusion: Further testing should be conducted in a larger sample to facilitate confirmatory factor analysis. The Health Belief Model for Shift Workers scale is likely to be beneficial for in future studies of interventions for shift workers.